Eight Hours Versus twenty four hours Postpartum Magnesium Sulphate for Prophylaxis in Women with Pre-Eclampsia - Sobia Mushtaq, Majida Zafar, Ayesha Ahmed, Aiman Asif, Munaza Jahan, Bushra Munir, Benish Ishaq, Zara Mahmood, Naima Sher (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the outcome of 8 hours versus 24 hours postpartum magnesium sulphate for eclampsia prophylaxis in women with moderate to severe pre-eclampsia. Study design: Randomized control trial Place and duration of study: The study was conducted in Gynecology and Obstetrics Department, MCH -1, PIMS Hospital, Islamabad from August 2020- Jan 2021 Methodology: After getting approval from hospital ethical committee and informed consent from patients the randomized controlled trial was conducted. The sample size was calculated by using WHO sample size calculator and total sample size was 108 patients that were selected after fulfilling of selection criteria. Complete history, physical examination, laboratory investigations and sonographical evaluation was performed for the selected women. The selected women were randomly assigned to either group A or B using a random list developed by lottery method. Group A received MgSO4 for 8 hour (8micro drops/min) and Group B received MgSO4 for 24 hours only (8micro drops/min). The primary outcome was occurrence of eclamptic fits and secondary outcomes were ambulation time, initiation of breast feeding, patient’s hospital stay and patient satisfaction in both groups. Data was analyzed by using SPSS version 21.0. P-value <0.05 was considered significant Results: Women in both groups had similar demographic profile. Baseline patients’ characteristics (systolic BP, diastolic BP, Hb, ALT and uric acid, urinary protein) were also similar in both groups. Main symptoms were headache, blurred vision and epigastric pain in both groups Eclamptic fits in the first 72 hours were not observed in both groups. In group A patients, mean ambulation time was 10.6±1.1 hours and in group B it was 18.8±7.5 hours (P=0.001). In group A patients, mean time to initiate breast feeding was 14.6 ± 1.9 hours and in group B it was 24.3±8.3 hours (P=0.001). In group A patients, mean duration of hospital stay was 2.8±0.43 days and in group B it was 3.4±0.49 days (P=0.001). In group A patients, mean patient satisfaction score was 8.9±1.1 and in group B it was 4.5±1.8 (P=0.001). Clinical implication:Less risk of side effects observed and less monitoring required. Conclusion:Both the dosing regimens were equally effective and eclamptic fits in the first 72 hours were not observed in both groups. Mean ambulation time, mean time to initiate breastfeeding and mean duration of hospital stay was significantly shorter in patient treated with MgSO4 for 8 hours compared to those treated with MgSO4 for 24 hours. Patients treated with MgSO4 for 8 hours demonstrated better satisfaction when compared to those treated with MgSO4 for 24 hours. Keywords: Postpartum magnesium sulphate, eclampsia, prophylaxis, pre-eclampsia. Ambulation time, Breastfeeding